The theory of the growth of the firm - Penrose, Edith Tilton (Oxford University Press, 2009)
There are not many books that are genuine classics, and only a handful in business and management whose insights and ideas last for 50 years and more. This book is one of the very few 'must reads' for anybody seriously interested in the role of management within the firm. Originally published in 1959, The Theory of the Growth of the Firm has illuminated and inspired thinking in strategy, entrepreneurship, knowledge creation, and innovation. Edith Penrose's tightly-argued classic laid the foundations for the resource based view of the firm, now the dominant framework in business strategy. She an.